DETERMINANTS OF DIARRHEA AND EFFORTS TO INCREASE PUBLIC KNOWLEDGE OF DIARRHEA IN PARENTS OF CHILDREN 6 MONTHS-5 YEARS OLD THROUGH MENTORSHIP IN KARANGDUREN VILLAGE, PAKISAJI HEALTH CENTER AREA - Shalshabilla, Nadya Neyza; Wardhani, Regita Kusuma; Damianna, Salma Karin; Alfani, M Naufal Rizqi; Prasetyo, M Budi; Arifin, Samsul; Rahmah, Shofi Nur (Universitas Brawijaya, 2024)
Diarrhea is the passage of three or more loose or liquid stools per day (or more frequent passage than is normal for the individual). Frequent passing of stools that have formed consistency is not diarrhea, nor is the passing of loose stools by babies under 6 months old who only consume breast milk. In many studies, it has been identified that factors related to diarrhea are mainly associated with adequate access to water, sanitation, and hygiene. Apart from these environmental factors, educational factors are also factors that influence the high incidence of diarrheal diseases, with low levels of education resulting in a lack of knowledge about diarrhea and Pola Hidup Bersih dan Sehat (PHBS). This research aims to determine the risk factors contributing to diarrhea in Karangduren Village, Pakisaji District, and determine the level of knowledge of the Karangduren Village community regarding the management and prevention of diarrhea. This research was conducted in 2 stages, pre-intervention and intervention stages. At the pre-intervention stage, a questionnaire was used as a research instrument to determine the level of community knowledge and behavior about diarrhea that met the inclusion criteria which was analyzed using the Chi-Square test. At the intervention stage, the pre-experimental method used a one-group pretest-posttest design to assess the knowledge about diarrhea before and after being given the intervention which was analyzed using the Wilcoxon Test. The intervention was carried out by providing education and providing ‘Buku Saku Diare’ through mentorship related to diarrhea and Pola Hidup Bersih dan Sehat (PHBS).The results of the risk factor analysis, show that the factors contributing to the high prevalence of diarrhea in Karangduren Village are closely related to knowledge and implementation of Pola Hidup Bersih dan Sehat (PHBS). The intervention group included 30 participants, and an increase in respondents' knowledge was obtained with a significant value of p=0.000 (p<0.05).The outreach intervention that has been carried out with educational media using the ‘Buku Saku Diare’ can increase community knowledge in Karangduren Village.